Is there an intergenerational discrepancy in the comprehension and aesthetic preference regarding emoji usage? Evidence from WeChat - Wu, Donghang; Zhang, Xinxiu; Zhang, Xinjia (Frontiers in Psychology, 2024)
Emojis are widely used on social media, blogs, and instant messaging to express users' feelings. However, in everyday interactions, the same emoji often has different interpretations and aesthetic preferences among different age groups. This can lead to communication barriers and misunderstandings. Based on social identity theory, this study uses WeChat, a social platform popular in China, to analyze intergenerational differences in emoji understanding and preferences through a questionnaire survey. The results indicate: (1) There are significant intergenerational differences in the usage habits, interpretation, and aesthetic preferences of emojis. (2) Middle-aged and elderly tend to interpret goodbye emoji symbols as simple emotional expressions, such as "goodbye" or "see you later," while younger-age groups lean towards more complex emotions and social intentions, such as "speechlessness" and "end of friendship." (3) Younger-age groups use emojis frequently and with a wide variety, whereas Middle-aged and elderly groups use emojis less frequently and with limited variety. Younger individuals' aesthetic preferences for emojis lean towards humor, conflict, and narrative, whereas Middle-aged and elderly groups prefer emojis with bright colors and everyday greetings typical of their generation. Based on research findings, we believe that social identity theory provides a framework for understanding how individuals establish their identities through interactions with specific social groups. This study is beneficial for identifying the comprehension and aesthetic biases in emoji usage across generations, sheds light on the broader implications of social identity theory in digital communication contexts, and promotes friendly social interactions in real-time communication applications.